Ayat dan Hadits Tentang Hal-Hal Penting dalam Manajemen Sumber Daya Manusia dalam Manajemen Pendidikan Islam - Fatrisna, Yuli; Bustamam, Risman; Mudarti, Hasni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to explore the concept of human resource management (HRM) from an Islamic perspective through the study of verses of the Qur'an and the hadiths of Prophet Muhammad SAW that discuss the essence, potential, and basic nature of humans. The method used is a qualitative approach with a type of library research. Data collection techniques are carried out through systematic exploration of tafsir books, hadith books along with their explanations, as well as relevant articles and scientific journals. Data analysis is conducted using content analysis and textual hermeneutics approaches to interpret the textual and contextual meanings of the verses and hadiths studied. The research results show that the concept of human resource management in Islam is comprehensive and holistic, as it not only emphasizes aspects of efficiency and productivity but also includes moral, spiritual, and social responsibility dimensions. This study also presents case studies of human resource management in several public and private schools both within and outside West Sumatra as an implementation of Islamic values in contemporary managerial practices. These findings affirm that Islamic human resource management prioritizes balanced competency development alongside spiritual nurturing, thereby fostering responsible and independent individuals